Pokroviteljstvo zagrebačkog biskupa Jurja Branjuga u Bologni: knjiga Vera ecclesia Christi Vincenza Lodovica Gottija s portretima mecene i autora. - Premerl, Daniel (Journal of the Institute of Art History, 2024)
In 1748, in Bologna, Zagreb's Bishop Juraj Branjug acted as the patron for the book Vera ecclesia Christi, authored by the prominent Catholic theologian Vincenzo Lodovico Gotti (Fig. 1). The book includes two engraved portraits: one of its patron, Bishop Branjug (Fig. 2) and another of its author, Gotti (Fig. 3), both created by the Bolognese engraver Giovanni Fabbri. The portraits of Branjug and Gotti were found in the Croatian State Archives and the Croatian History Museum, where they had arrived cut out from the book, making their origins and the context of their production unclear. Vincenzo Lodovico Gotti (1664-1742) was one of the leading Catholic theologians of his time. He taught theology at the University of Bologna until 1728, when he was elevated to the cardinalate and transferred to Rome. During his tenure in Bologna, he also taught at the Illyrian-Hungarian College, a national college affiliated with the University of Bologna and owned by the Zagreb Cathedral Chapter. Juraj Branjug was one of Gotti' s students there from 1699 to 1702, before becoming Bishop of Zagreb in 1723 (confirmed in 1727). The translator of the Vera ecclesia Christi was Vincenzo Tommaso Covi, who succeeded Gotti as a professor at the Illyrian-Hungarian College in 1728. Covi also authored the dedicatory preface to Branjug, which opens the book (Fig. 2). In this preface, Covi, a Dominican theologian from Bologna, explains that he translated Gotti' s work into Latin to make it accessible to a broader audience. He argues that since the book had successfully refuted Protestant theological arguments along Italy's borders, it could be equally useful in other parts of the world, in polemics with non-Catholics and their conversion. For this purpose, Covi chose Bishop Branjug as the book's patron, justifying his choice by emphasizing Branjug's admiration for Gotti' s lectures at the Illyrian-Hungarian College in Bologna and his exceptional debating skills. The engraved portrait of Bishop Branjug and the background bear a strong resemblance to his painted portraits in Zagreb, housed in the Archbishop's Palace, the Croatian History Museum (Fig. 4), and the Museum of Arts and Crafts. It is likely that Giovanni Fabbri based his engraving on a now-lost painted portrait of Branjug that once hung in the Illyrian-Hungarian College in Bologna, where portraits of Zagreb bishops were traditionally displayed. The following introductory chapter by the translator, De vita Auctoris, features a portrait of Vincenzo Lodovico Gotti (Fig. 3). His facial features and attire - including his prominent nose, a lock of hair visible under his cap, and a characteristic collar - closely resemble details in his painted portrait in the University Library of Bologna and his engraved portrait from the book Effigies Cardinalium nunc viventium (Fig. 6). Fabbri' s engraved portrait of Gotti is most similar to the painted portrait housed in the Croatian History Museum (Fig. 7). Given that this painted portrait stylistically points to an Italian master, and closely resembles the engraved version discussed here, it is plausible that this was the portrait from the Illyrian-Hungarian College in Bologna mentioned in the college' s 1732 inventory, which served as the model for the engraving. The painted portrait was likely commissioned by Bishop Branjug, as suggested in a letter from the college rector to Branjug in July 1728. The portrait of Cardinal Gotti eventually found its way to the Croatian History Museum via the collection of Ivan Kukuljević Sakcinski, possibly through his grand-uncle Vuk (Wolfgang) Kukuljević, a prominent Zagreb canon close to Branjug. The Illyrian-Hungarian College in Bologna emerges as the central hub connecting all participants in this publishing project. The 1748 edition of Gotti' s Vera ecclesia Christi is not only a significant theological work, but also an integral part of the cultural and artistic heritage of the Illyrian-Hungarian College in Bologna. The author of the portraits in the book, Giovanni Fabbri (?-1777), was a highly regarded Bolognese engraver of his time. Eighteen years later, he again worked on commissions for Croatian patrons in Bologna, producing an engraving of the catafalque for Emperor Francis I, based on a drawing by Mauro Tesi (Fig. 9), which was published in 1766 in the av-viso De funereFrancisciRomanorum electiImperatoris (....). The relationship between Branjug and Gotti was one of mutual admiration and lifelong respect. The preface to the Vera ecclesia Christi describes Branjug as one of Gotti' s favourite students, a view echoed by Baltazar Adam Krčelić and Grgur Josip Gašparić in their writings. Later documents confirm the enduring friendship. For instance, in 1728, Cardinal Gotti thanked Branjug for his congratulatory letter upon his elevation to the cardinalate. Subsequently, at Branjug' s request, Gotti helped secure papal approval from Pope Clement XII in 1735 allowing Zagreb canons to wear the rocchetto and the mozzetta. Additionally, Krčelić and Gašparić record that Branjug sent gifts to Cardinal Gotti. Indeed, a letter in Branjug' s correspondence reveals that in 1739, he commissioned a silver set from the Viennese goldsmith Mayr, which was sent to Gotti in Rome the following year (described as a pelvis argentea cum suo fusorio, nec non duo candelabra argentea cum suo emunctorio). Branjug' s patronage of the Vera ecclesia Christi was both a personal expression of gratitude and a means of self-representation. However, it also symbolized the collective esteem of the Zagreb Church for both the universal Catholic Church and the University of Bologna as the institutional framework of higher education in the Zagreb Diocese. With this book edition, safeguarded by the watchful portraits of the Croatian bishop and the Italian theologian and cardinal, the Diocese of Zagreb presented and positioned itself within the international network of Catholic theological excellence and prestige.